2022
DOI: 10.1371/journal.pone.0272751
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of Immunoglobulin G (IgG) and IgM antibodies to SARS-CoV-2 in asymptomatic and symptomatic individuals amidst vaccination roll-out in western Kenya

Abstract: The population’s antibody response is a key factor in comprehending SARS-CoV-2 epidemiology. This is especially important in African settings where COVID-19 impact, and vaccination rates are relatively low. This study aimed at characterizing the Immunoglobulin G (IgG) and Immunoglobulin M (IgM) in both SARS-CoV-2 asymptomatic and symptomatic individuals in Kisumu and Siaya counties in western Kenya using enzyme linked immunosorbent assays. The IgG and IgM overall seroprevalence in 98 symptomatic and asymptomat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(40 reference statements)
4
6
0
Order By: Relevance
“…This finding is in agreement with others at a similar time in the continent: serosurveys in Cameroon, Gambia, Uganda and South Africa have reported antibody positivity between 87% and 96% during the Omicron wave 16,17,19,50,54 . Although lower, the 76.5% seroprevalence reported in Kenya by Awandu et al greatly surpasses PCR confirmed cases 25 . A 2022 rapid‐assay based survey in the Republic of the Congo reported a much lower seroprevalence (48.2%) 15 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is in agreement with others at a similar time in the continent: serosurveys in Cameroon, Gambia, Uganda and South Africa have reported antibody positivity between 87% and 96% during the Omicron wave 16,17,19,50,54 . Although lower, the 76.5% seroprevalence reported in Kenya by Awandu et al greatly surpasses PCR confirmed cases 25 . A 2022 rapid‐assay based survey in the Republic of the Congo reported a much lower seroprevalence (48.2%) 15 .…”
Section: Discussionsupporting
confidence: 91%
“…A recent study in Uganda found that 85% of previously negative participants had detectable antibody levels post‐Omicron 54 . It has been suggested that this drastic increase could have been favored by a reduction in perceived danger and pandemic fatigue, 25 as the rate of transmission is highly related to population density, hygiene, and the observation of nonpharmacological interventions. Nevertheless, adherence to these public health measures was generally low in the DRC, however, higher in the capital than in other regions 56 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Other studies in Africa also measured higher SARS-CoV-2 seroprevalence among vaccinated participants, higher neutralizing antibody titers among participants with infection and vaccination, and faster waning of antibodies post-vaccination among participants who had not been infected. 7,2729 These results support the recommendation for COVID-19 vaccination (including booster doses) regardless of past infection. COVID-19 vaccination campaigns were conducted throughout Zambia during the study period, but vaccine coverage among study participants was lower than the general population, possibly reflecting hesitancy toward vaccination during pregnancy, and only about 12% of the fully vaccinated population has received a booster dose.…”
Section: Discussionsupporting
confidence: 74%